2007
DOI: 10.1002/pen.20858
|View full text |Cite
|
Sign up to set email alerts
|

Optical monitoring of polypropylene crystallization during injection molding

Abstract: The nonisothermal crystallization of polypropylene resins, i-PP, during injection molding, using an optical device inserted in the injection mold cavity was monitored. The device detected the change of optical properties which occurs in polymers during their crystallization process; thus the intensity of a laser beam after it passed through the crystallizing polymer was measured during an injection molding cycle. The collected light intensity after the end of the cycle was correlated with the morphologies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…The thickness of the skin of all of the samples was measured, and it is shown in Table ; we observed that, as expected, the lower Q was, the lower the shear rate and the higher the time for the beginning of the flow‐induced crystallization to occur were, as confirmed by other works . Therefore, the thickness of the frozen skin layer was higher.…”
Section: Resultssupporting
confidence: 78%
“…The thickness of the skin of all of the samples was measured, and it is shown in Table ; we observed that, as expected, the lower Q was, the lower the shear rate and the higher the time for the beginning of the flow‐induced crystallization to occur were, as confirmed by other works . Therefore, the thickness of the frozen skin layer was higher.…”
Section: Resultssupporting
confidence: 78%
“…An iron-constantan thermocouple was used to check the mold temperature periodically. The mold cavity had disk geometry, with diameter of 90 mm and thickness of 2 mm, a sapphire window to optically monitor each injection molded cycle and a pressure transducer, as already described in our previous work 40 . The polymer was injected through the center of the cavity, as shown in Figure 1a.…”
Section: Injection Moldingmentioning
confidence: 99%
“…Table 2 shows the analyzed molding conditions. These analyzed conditions were chosen based on early study 40 that shows that the mold temperature and flow rate are the parameters that affected most the kinetics of crystallization of these polymers in this particular disk geometry.…”
Section: Injection Moldingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that during the injection molding of semicrystalline polymers, the melt is subjected to complicated stress and temperature fields before crystallization. Thus, for a semicrystalline polymer, such as polypropylene (PP), the thermomechanical history is expected to significantly influence the crystallization process and crystalline structures, resulting in the hierarchical crystalline structures in the molded parts [ 1–5].…”
Section: Introductionmentioning
confidence: 99%